About a Brief Biography of Third Yalguusan Khutugtu Luvsandambadarjai - Torguud, Otgonbayar (Tibetan Studies, 2024)
The biography of Luvsandambadarjai (1757-1819), the third Yalguusan khutugtu of Zasagt Khan province, was written by Gungtang Konchok Tenpai Dronme (1762-1823) in the Tibetan, who lived at the same time as him. In the past, there was no written biography of this third Yalguusan khutugtu in the Tibetan, but many documents such as letters, letters of appeal, and all Yalguusan khutugtu originals documents, written in Mongolian script have been preserved in the archive. The biography in Tibetan that we found is 11 pages in long block print, and the information written in it contributes to correcting some information that may have been mistakenly recorded in the Mongolian script archive documents or may have been mistakenly written down in Cyrillic. This article will briefly mention the information contained in the biography, which will be an important contribution to the accurate clarification of the life and writings of Lama Luvsandambadarjai because it was written by a person who lived at the same time. Ялгуусан хутагтын III дүр Лувсандамбадаржаагийн товч намтрын тухай Хураангуй: Засагт хан аймгийн Ялгуусан хутагтын III дүр Лувсандамбадаржаа (1757-1819) ламын намтрыг өөртэй нь нэг цаг үед амьдарч асан Гүнтан гэгээн Гончогдамбийдонмэ (1762-1823) лам төвөд хэлээр зохиосон ажээ. Урьд өмнө нь уг III дүрийнх нь төвөд хэлээр бичигдсэн намтар мэдэгдээгүй боловч монгол бичгээр бичигдэж үлдсэн захиа, өргөх бичиг, Ялгуусан хутагтуудын уг эх зэрэг олон баримт мэдээ архивд хадгалагдан үлджээ. Бидэнд олдсон төвөд хэлээрх намтар нь урт барын 10 хуудас бөгөөд дотор нь тэмдэглэгдсэн мэдээ сэлт нь монгол бичгээр буй архивын баримтад ташаарч тэмдэглэгдсэн юм уу эсвэл кирилл үсэгт буулгахдаа андуурч буулгасан байж болохуйц зарим мэдээллийг залруулахад бага боловч нэмэр болохоор байна. Нэг цаг үед амьдарч байсан хүн зохиосон учраас Лувсандамбадаржаа ламын амьдрал, зохиол үйлсийг үнэн зөвөөр тодруулахад чухал хувь нэмэр болохуйц уг намтрын доторх мэдээллийн талаар өгүүлэх юм. Түлхүүр үг: Засагт хан аймгийн Ялгуусан хутагт, Лувсандамбадаржаа, намтар зохиол